Tracing Immunological Interaction in Trimethylamine N-Oxide Hydrogel-Derived Zwitterionic Microenvironment During Promoted Diabetic Wound Regeneration - Li, Zheng (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.